The Last Mile: Turning Public Policy Upside Down - Amarjeet Sinha (Routledge India, 2024)
The Last Mile explores the gaps and dichotomy between drafted policies and their implementation, and the last mile challenges which often make public services inaccessible to the poorest and most vulnerable sections of society. It provides an in-depth overview of the dynamics between communities, research and consultation and the implementation of policies for development. Rich in empirical data and case studies from different government programmes and reports, this book examines the implementation of government service programmes for poverty reduction, women's empowerment, and income generation for the poor, among others, from a people's perspective. It highlights the need for policies and institutions to align their methods to community needs. Offering guidelines for redesigning as well as solutions to counter challenges related to lack of trust and effective communication, human resource management, capacity development, redressal mechanisms, and facilitating the last mile connection, the author delineates effective ways for integrating new technologies in policy implementation. The book also addresses legacy issues in institutions and re-orienting policy for better governance, transparency, and building trust. Part of the Innovations, Practice and the Future of Public Policy in India series, this book, by a senior practitioner, will be an essential resource for students and researchers of development studies, sociology, public policy and governance, economics, and South Asian studies. This book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons (CC-BY-NC-ND) 4.0 license.
Keywords: 360; community development; governance; public policy; social programmes; socioeconomic development